Tumor microenvironment and immune-related myositis: addressing muscle wasting in cancer immunotherapy - Ma, Shuang; Zhao, Guangyu; Sui, Shang; Chen, Xiankai; Wu, Linxin; Wang, Taihang; Xu, Wanying; Lu, Zhijiao; Wang, Andong; Wu, Xiaolin; Wu, Jiaxuan; Liu, Yi; et al. (Frontiers in Immunology, 2025)
Cancer immunotherapy, which leverages the immune system to target neoplastic cells, has undergone significant transformation in recent. However, immunotherapy may have negative effects on skeletal muscle function, causing muscle wasting and functional decline in cancer patients. In this study, we review the mechanisms by which immunotherapy influences skeletal muscle, focusing on immune-related myositis, inflammation, and metabolic alterations within the tumor microenvironment (TME). The key methodologies, including biomechanical assessment techniques such as electrical impedance myography and ultrasound imaging, are discussed to provide valuable insights into process that maintain muscle integrity and function in patients receiving immunotherapy. Moreover, the dual effects of immunotherapy on tumor suppression and muscle damage are described, revealing the significance of inflammatory cytokines, immune checkpoints, and metabolic disturbances within the TME. Importantly, we propose combination therapies integrating immunotherapy and nutritional interventions or anti-inflammatory interventions as potential approaches for mitigating muscle wasting. This study highlights the need for deeper investigations to optimize immunotherapy and improve its efficacy in preserving muscle health, thereby improving patient outcomes and quality of life.